Ethnomathematics-based examination of logical reasoning and measurement within the sritanjung and sidapaksa legend for mathematics education - Alex Haris Fauzi; Marsida Aulia Rahma; Risma Nisa Insyiroh; Siti Nur Laili; Alfina Rizki (LINEAR: Journal of Mathematics Education, 2026)
This study is motivated by the need for contextual and culturally grounded mathematics learning, as well as the limited research exploring ethnomathematics through folklore, particularly the Sritanjung and Sidapaksa legend. This research aims to analyze elements of logical reasoning and quantitative measurement within the legend and to describe its potential as a source for contextual mathematics instruction. Employing a descriptive qualitative design with an ethnographic approach, data were collected through the documentation of narrative text and a literature review, and then analyzed through data reduction, classification, interpretation, and verification. The results indicate that the Sritanjung and Sidapaksa legend contains logical reasoning structures, such as cause–and–effect relations, implications, analogies, and moral reasoning. Measurement elements, on the other hand, appear in the description of Sidapaksa’s journey, which relates to distance, time, speed, and spatial representation through maps and scales. These findings demonstrate that folklore can serve as an effective source of ethnomathematics for contextualizing mathematical concepts while simultaneously strengthening cultural values and character development. This research contributes to the expansion of ethnomathematics studies based on oral literature, which previously focused more on physical cultural artifacts. The identified logical reasoning and quantitative measurement concepts are particularly relevant for junior secondary school (7th and 8th grade) mathematics learning.